IMPLEMENTASI PEMBELAJARAN BERBASIS VIDEO ANIMASI INTERAKTIF UNTUK MENINGKATKAN PEMAHAMAN PESERTA DIDIK PADA MATERI FOTOSINTESIS DI KELAS V SDN SUKARAJA 2 - Sulistiawati; Novia Hani Safitri; Rika Amelia; Widiyawati; Asri Rismayanti; Rana Gustian Nugraha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Social studies learning in elementary schools often faces obstacles because the material tends to be more complex and abstract, making it difficult for students to understand the abstract process of photosynthesis and the use of conventional learning methods that do not actively involve students. This also occurs in fifth- grade students who do not yet understand the overall concept of photosynthesis. This study aims to improve the understanding of fifth-grade students at SDN Sukaraja 2 of photosynthesis material through the use of interactive animated video- based learning media combined with simple experimental methods, particularly in the process of photosynthesis. The research method used was Classroom Action Research (CAR) with the Kemmis and McTaggart model, which was carried out in two cycles, each cycle covering the stages of planning, implementation of actions, observation, and reflection. The research subjects consisted of 29 fifth-grade students at SDN Sukaraja 2. Data collection techniques were carried out through learning outcome tests and observation of student activities during the learning process. Data were collected through learning outcome tests, observation of student activities during the learning process, and documentation. The results showed an increase from cycle I to cycle II of 27.5%. This had a positive effect on student understanding in each cycle, as indicated by increased learning outcomes and student activity in participating in learning. In cycle II, most students achieved scores above the Minimum Passing Grade (MPG) of 75. Thus, the use of interactive animated videos and simple experiments proved to be effective in improving students' understanding of photosynthesis, especially the process of photosynthesis, and can be used as an alternative learning medium to improve and refine the learning process in elementary schools.